Bliss Wedding Gallery / Musalmah Abd. Rahim ... [et al.] - Abd. Rahim, Musalmah; Alias, Liaeriana; Sarif, Norhafiza; Tahar, Nuratiqah; Basri, Norfaezah (Faculty of Office Management & Technology, 2006)
The business proposal gives us an opportunity to indulge ourselves in the field of entrepreneurship and for us to acquire the tricks of the trade in the world of business. This proposal also taught us on how to run and manage a business wisely and to gain maximum profit. In running our business, we as the partners of Bliss Wedding Gallery decide to operate our business activity at Section 9, Shah Alam. This is because, we have already observed this location and found out that is a productive place to runs our business. We also found out them not most of the business, thus giving us the advantage to start our business there with limited competitors. However, we also do not deny that we also have to compete in this business in that area of Shah Alam. But we view the existence of these competitors in a positive manner because the competition will encourage us to run our business at the best level and in a competitive way.